Ambulatory management of pneumothorax using a novel device: Rocket Pleural Vent. Issue 5 (6th May 2019) - Jones, Laura; Johnston, Robert; Aujayeb, Avinash
Abstract : Pneumothorax management is controversial with no clear agreement for optimum management. The British Thoracic Society suggests needle aspiration first line in primary pneumothorax and the American Thoracic Society advises intercostal drain insertion. The European Respiratory Society task force also suggests needle aspiration in primary pneumothorax and adopts an overall more conservative approach. Ambulatory pneumothorax management has been described for 40 years and recommended in the 2010 British Society pleural guidelines, although overall quality of studies was poor. A new device, the Rocket Pleural Vent (PV) has been on the market for 4 years now and randomised controlled trials are under way, although there are case series suggesting efficacy and low complication rates. The PV allows ambulatory management of pneumothorax. Local guidelines have been developed and 18 devices have been placed in 6 months. We describe our experience based on a patient.